The effect of ß-alanine supplementation on high intensity cycling capacity in normoxia and hypoxia - Patel, K. A.; de Oliveira, L. F.; Sale, C.; James, R. M. (Journal of Sports Sciences, 2021)
The availability of dietary beta-alanine (BA) is the limiting factor in carnosine synthesis within human muscle due to its low intramuscular concentration and substrate affinity. Carnosine can accept hydrogen ions (H+), making it an important intramuscular buffer against exercise-induced acidosis. Metabolite accumulation rate increases when exercising in hypoxic conditions, thus an increased carnosine concentration could attenuate H+ build-up when exercising in hypoxic conditions. This study examined the effects of BA supplementation on high intensity cycling capacity in normoxia and hypoxia. In a double-blind design, nineteen males were matched into a BA group (n = 10; 6.4 g/d) or a placebo group (PLA; n = 9) and supplemented for 28 days, carrying out two pre- and two post-supplementation cycling capacity trials at 110% of powermax, one in normoxia and one in hypoxia (15.5% O2). Hypoxia led to a 9.1% reduction in exercise capacity, but BA supplementation had no significant effect on exercise capacity in normoxia or hypoxia (P > 0.05). Blood lactate accumulation showed a significant trial x time interaction post-supplementation (P = 0.016), although this was not significantly different between groups. BA supplementation did not increase high intensity cycling capacity in normoxia, nor did it improve cycling capacity in hypoxia even though exercise capacity was reduced under hypoxic conditions.